Learning Journal as A Tool to Show Students’ Understanding in Learning Analysis of School Curriculum (RETAIN, 2020)
Abstrak Jurnal pembelajaran merupakan catatan pemikiran siswa selama kegiatan belajar mengajar yang memiliki beberapa kriteria. Bagaimanapun, siswa tidak menyangkup semua criteria tersebut. Tujuan dari penelitian ini yaitu mendeskripsikan sejauh mana jurnal pembelajaran siswa menyangkup kriteria yang diberikan. Desain penelitian dari penelitian ini adalah kualitatif. Subjek dari penelitian ini yaitu tiga mahasiswa dari jurusan Bahasa Inggris di salah satu universitas negeri di Surabaya, dan seorang dosen sebagai subjek pendukung dalam pengumpulan data. Wawancara semi terstruktur dan dokumen pra-rekaman digunakan untuk mengumpulkan data. Kemudian, data yang terkumpul dianalisis dan dijabarkan secara spesifik berdasarkan interpretasi peneliti secara deskriptif. Dengan demikian, temuan telah menunjukkan lima kesimpulan. Pertama, Jurnal siswa memenuhi kriteria pertamasebagai tugas individu. Kedua, jurnal siswa memenuhi kriteria untuk menulis berdasarkan topik dari guru. Ketiga, jurnal siswa melengkapi kriteria untuk memberikan deskripsi singkat materi. Keempat, jurnal siswa tidak memenuhi kriteria pemberian ide tambahan terhadap materi ajar. Kelima, jurnal siswa memenuhi kriteria keterampilan penyelesaian masalah. Kata Kunci: jurnal pembelajaran, media, pembelajaran. Abstract A learning journal is a kind of record of the students’ thought during teaching and learning materials which have several criteria. However, students do not fulfil the whole criteria of writing learning journals. The purpose of this study was to describe the extent to which learning journal written by students fulfil the criteria given. The basic interpretive research of this study used a qualitative approach. The subjects of this study were three students from the English Department in one of a university in Surabaya, and the teacher as the supporting subject in collecting the data. The semi-structured interview and prerecorded documents were applied to collect the data. Then, the data obtained were analyzed and explained specifically based on the researcher’s interpretation descriptively. Thus, the findings have shown five conclusions. First, the students complete the criteria as an individual task. Second, the students complete criteria to write based on topics given by the teacher. Third, the students complete the criteria to describe the materials. Fourth, the students did not complete criteria to give additional ideas toward learning materials. Fifth, the students complete criteria to solve their problems in learning materials. Keywords: learning journal, tool, learning